Pengaruh Konsumsi Jus Buah Bit (Beta vulgaris L) Terhadap Kadar Hemoglobin Mahasiswa Putri di Condongcatur, Sleman - Kumara Rahmawati Zain; Gravinda Widyaswara; Shinny Love Laga Hae; Wiwit Sepvianti; Arif Tirtana; Sunartono Sunartono; Siti Arifah (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Hemoglobin is the main element of red blood cells that functions as a conjugated protein to transport oxygen and carbon dioxide. Hemoglobin levels below normal limits can cause anemia. Indonesia is one of the countries with a fairly high rate of anemia. Anemia is a common health problem among adolescent girls, mainly caused by iron deficiency which is triggered by menstruation and high nutritional needs. Currently, a non-pharmacological approach is an alternative to increase hemoglobin levels in adolescent girls, one of which is by consuming beetroot juice. Indonesia is one of the countries with relatively high anemia rates. Beetroot is rich in iron, folate, and vitamin C which can increase hemoglobin levels in the blood. The type of research used was a quasi-experimental study with a two-group pretest and posttest design, namely providing intervention by giving beetroot juice for 7 days in the morning to students in the eastern region who live in Condongcatur, Depok, Sleman, Yogyakarta. The results of this study were explained using SPSS with a Paired sample t-test with a p value <0.05 and obtained H0 = 0.024 and H7 = 0.001. This means that the sig value <0.05 indicates an effect on hemoglobin levels after the intervention. Before the intervention, the average was 11.1 gr/dl and after the intervention, the average was 12.8 gr/dl. These results indicate that consumption of beetroot juice can significantly increase hemoglobin levels in adolescent girls with anemia.